Impact of plasma and follicular fluid BMP15 levels on ICSI-ET cycle outcome - Sapmaz, E.; Ozkan, Z.; Ilhan, R.; Simsek, M.; Ekinci, M.; Timurkan, H. (Oxford Univ Press, 2014)
[Abstract Not Available]
30th Annual Meeting of the European-Society-of-Human-Reproduction-and-Embryology (ESHRE) -- JUN 29-JUL 02, 2014 -- Munich, GERMANY